2002
DOI: 10.1002/neu.10036
|View full text |Cite
|
Sign up to set email alerts
|

Novel UNC‐44 AO13 ankyrin is required for axonal guidance in C. elegans, contains six highly repetitive STEP blocks separated by seven potential transmembrane domains, and is localized to neuronal processes and the periphery of neural cell bodies

Abstract: Conventional ankyrins are cortical cytoskeletal proteins that form an ankyrin-spectrin meshwork underlying the plasma membrane. We report here the unusual structure of a novel ankyrin (AO13 ankyrin, 775,369 Da, 6994 aa, pI = 4.45) that is required for proper axonal guidance in Caenorhabditis elegans. AO13 ankyrin contains the ANK repeat and spectrin-binding domains found in other ankyrins, but differs from all others in that the acidic carboxyl region contains six blocks of serine/threonine/glutamic acid/proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
(45 reference statements)
2
28
0
1
Order By: Relevance
“…Neither insertion disrupted unc-44 function, as the knock-in animals superficially resembled the wild type in movement and growth rate. In adults, the pattern of UNC-44C::GFP( ju1413) fluorescence was generally consistent with that described for UNC-44 common isoforms by immunostaining (Otsuka et al, 2002); however, we also observed strong expression in muscles and in gonadal spermathecal/sheath cells (Fig. 1B, upper panel).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Neither insertion disrupted unc-44 function, as the knock-in animals superficially resembled the wild type in movement and growth rate. In adults, the pattern of UNC-44C::GFP( ju1413) fluorescence was generally consistent with that described for UNC-44 common isoforms by immunostaining (Otsuka et al, 2002); however, we also observed strong expression in muscles and in gonadal spermathecal/sheath cells (Fig. 1B, upper panel).…”
Section: Resultssupporting
confidence: 87%
“…S1A). The N-terminal common domains of the major UNC-44 isoforms contain multiple ankyrin repeats and a spectrin-binding domain followed by a regulatory domain (Otsuka et al, 2002). Previous studies of UNC-44 expression used antibodies raised against the spectrin-binding domain, the conventional regulatory domain, or the extended C-terminal set of STEP domains specific to the large isoform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Section 1734 solely to indicate this fact. (23,24). We have used small interfering RNA (siRNA) encoded by a plasmid (25) to knock down the transcript encoding 190-kDa ankyrin-G in a polarized human bronchial epithelial cell line.…”
mentioning
confidence: 99%